An insight into brucellosis in wild boar and domestic pigs in Europe: a systematic review - Ruano, Zita Martins (2025)
In some European countries, animal brucellosis is a concern that requires a comprehensive understanding of its distribution, hosts and transmission routes, particularly involving wild species, in which the disease is still neglected. This systematic review was designed to summarize the current knowledge on the epidemiology of brucellosis in wild boar and domestic pigs in Europe. A systematic search was conducted in four databases to identify relevant original research articles. Thirty-six articles were included. Brucellosis has been identified in 17 European countries and the most reported circulating Brucella species and biovar was Brucella suis biovar 2. Brucella suis biovar 1, Brucella suis biovar 3, Brucella melitensis biovar 3 and Brucella microti were also identified from molecular investigations. We highlight the diversity in the occurrence of this infection, with the presence of Brucella species with zoonotic potential, and emphasize the need for surveillance.